When interlocutor’s face-language matching alters: An ERP study on face contexts and bilingual language control in mixed-language picture naming - Zhuang, Binyuan; Liang, Lijuan; Yang, Jing (Frontiers in Psychology, 2023)
The present study used event-related potentials (ERP) to examine the influence of face contexts on reactive and proactive language control in unbalanced Chinese-English bilinguals. They performed mixed-language picture naming task in a 25% face-language matched session, a baseline session without faces, and a 75% face-language matched session. For reactive language control, behavioral results showed an asymmetrical switch cost with larger switch cost in L1 in the 75% session, a reversed asymmetrical switch cost larger for L2 in the 25% session, and no switch cost in baseline session. ERP results revealed significantly different neural switch cost patterns in N2 and LPC amplitudes in the three sessions. For proactive language control, the reversed language dominance and larger LPC amplitudes during L2 naming were stable across the three sessions. Our findings suggest that reactive but not proactive language control is modulated by the ever-changing facial contexts, which highlights the highly flexible bilingual control systems subserving non-linguistic cues.